2022
DOI: 10.1002/1878-0261.13205
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification of indeterminate thyroid nodules by novel multigene testing: a study of Asians with a high risk of malignancy

Abstract: Molecular testing of indeterminate thyroid nodules informs about the presence of point mutations, insertions/deletions, copy number variants, RNA fusions, transcript alterations and miRNA expression. American Thyroid Association (ATA) guidelines suggest molecular testing of indeterminate thyroid nodules may be considered to supplement risk of malignancy (ROM). Although these recommendations have been incorporated in clinical practices in the United States, molecular testing of indeterminate thyroid nodules is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…For the DNA-RNA classifier, the sensitivity, specificity, PPV, and NPV were 88.4%, 53.3%, 84.4% and 61.5%, respectively. This study showed that the PPV for the DNA-RNA and the RNA classifier were higher (84.4% and 81.6% vs. 37.4% and 63.3%) and the NPV were lower (61.5% and 66.7% vs. 94.3% and 90.9%) than those of Afirma GEC and ThyroSeq v3 in their cohort [ 98 ]. The result of this study is showing that in an environment with high ROM among ITNs, like these Asian countries, the molecular testing may be more useful as a rule in test rather than a rule out test.…”
Section: Discussionmentioning
confidence: 99%
“…For the DNA-RNA classifier, the sensitivity, specificity, PPV, and NPV were 88.4%, 53.3%, 84.4% and 61.5%, respectively. This study showed that the PPV for the DNA-RNA and the RNA classifier were higher (84.4% and 81.6% vs. 37.4% and 63.3%) and the NPV were lower (61.5% and 66.7% vs. 94.3% and 90.9%) than those of Afirma GEC and ThyroSeq v3 in their cohort [ 98 ]. The result of this study is showing that in an environment with high ROM among ITNs, like these Asian countries, the molecular testing may be more useful as a rule in test rather than a rule out test.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation is that the rate of malignancy of ITNs in China may be underestimated. A study that recruited 140 samples in China showed that the malignant rate was 74.1% for resected ITNs [60]. Another multicenter study in Israel included 810 patients and indicated that the malignancy rates were higher than those reported earlier.…”
Section: Discussionmentioning
confidence: 90%
“…A study that recruited 140 samples in China showed that the malignant rate was 74.1% for resected ITNs. (42) Another multicenter study in Israel included 810 patients and indicated that the malignancy rates were higher than those reported earlier.…”
Section: Discussionmentioning
confidence: 91%